Polymeric Molecular Design Towards Horizontal Zn Electrodeposits at Constrained 2D Zn2+ Diffusion: Dendrite‐Free Zn Anode for Long‐Life and High‐Rate Aqueous Zinc Metal Battery - Xie, Dan; Wang, Zhi‐Wei; Gu, Zhen‐Yi; Diao, Wan‐Yue; Tao, Fang‐Yu; Liu, Chang; Sun, Hai‐Zhu; Wu, Xing‐Long; Wang, Jia‐Wei; Zhang, Jing‐Ping (Advanced functional materials, 2022)
Aqueous zinc metal batteries have garnered unprecedented attention owing to their high theoretical specific capacity, appropriate redox potential, and remarkable sustainability. Nevertheless, the intractable issues induced by the notorious Zn dendrite growth and serious interfacial side reactions significantly impede their large‐scale utilization. Inducing Zn to electrodeposit through parallel arrangement mode is critical to realizing dendrite‐free Zn metal anodes (ZMAs). To realize this purpose, a unique polymeric molecular design strategy through chemically grafting a thin polyanthraquinone (PAQ) overlayer on the Zn surface in the manner of spontaneous polymerization reaction of anthraquinone diazonium tetrafluoroborate (AQN2+BF4−) is proposed firstly. Impressively, thus‐derived PAQ overlayer as an artificial protective layer can constrain the Zn2+ ions 2D diffusion and homogenize the electric field and Zn2+ ions concentration distribution, further guiding preferential growth along the Zn(002) plane. Assisted by the PAQ overlayer, the dendrite growth, H2 evolution reaction, and Zn corrosion on ZMAs are suppressed effectively. Accordingly, such polymeric molecular modified ZMAs ensure a remarkably high Coulombic efficiency of 99.7% at 4 mA cm−2 and achieve a long cycling lifespan up to 1750 h at 1 mA cm−2 and superior rate capability. This work provides a new insight into designing an interface protective layer for achieving highly stable ZMAs. A unique polymeric molecular design strategy through chemical grafting of a thin polyanthraquinone overlayer on the Zn anode surface in the manner of spontaneous polymerization reaction of anthraquinone diazonium tetrafluoroborate (AQN2+BF4−) is first proposed to constrain Zn2+ 2D diffusion and realize the oriented growth of (002) crystal plane, then successfully suppressing the dendrite growth and H2 evolution reaction.